Experiences and Strategies of Talipapa Vendors in Transitioning to The New Normal - Patricia Denise Co; Erika Grizzel L. Florentino; John Paulo R. Gacias; Angelika Mae T. Maglasang; Nicole Shane G. Ojano; Karen Joy Catacutan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study explored the experiences, strategies, and accounting practices of talipapa vendors in Tuguegarao City during their transition to the new normal. The data were extracted by interviewing the informants using a questionnaire. The data were analyzed using thematic analysis. Three major themes were drawn, namely their experiences, strategies, and accounting practices they incorporated. The results revealed that majority of the informants had negative experiences but were able to survive using short-term strategies they implemented in their business operations and promotion or marketing, mainly targeted towards product and business innovation along with good customer service. On accounting practices, almost half the informants said they have basic accounting practices like bookkeeping and computing expenses and receivables